Insulin-like Growth Factors in a clinical setting: Review of IGF-I - Frysak, Zdenek; Schovanek, Jan; Iacobone, Maurizio; Karasek, David (Biomedical papers, 2015)
Background and Aims: Interest in growth hormone (GH) is inextricably linked to the need for in depth understanding of the somatomedins (insulin-like growth factors) which are polypeptides structurally similar to insulin and with broad physiological activity. To date, the most commonly known is Insulin-Like Growth Factor I (IGF-I). Despite considerable current knowledge of IGF-I, however, its bioactivity is incompletely understood. Measurement of IGF-I is of the utmost importance in the diagnosis and treatment of, for example acromegaly and growth hormone deficiency. The development of recombinant IGF-I, has allowed its use in such cases. Clinical practice, however, shows that few young/adult patients will benefit from treatment with the rIGF-I, mecasermin, given the number of adverse effects found. This review focuses on current knowledge mainly related to IGF-I and the use of its recombinant form (rIGF-I) in clinical practice. Several functions of IGI-II have been elucidated but their clinical significance is unclear.
Keywords: Somatomedins; Insulin-Like Growth Factor I; II; IGF-I receptor; Human Growth Hormone; Recombinant Human Growth Hormone; Acid Labile Subunit; IGF Binding Proteins; Mecasermin; Insulin Receptor Isoform A; acromegaly; growth hormone deficiency